Phytosynthesis And Structural–Optical Study Of Ag/Ag₂O Nanoparticles Using Mixture Of Leaves And Immature Fruits Extract Of Iraqi Christ’s Thorn (Journal of the College of Basic Education, 2026)
This study reports a novel green and straightforward method for synthesizing silver/silver oxide nanoparticles (Ag /Ag2O NPs) using a mixture of immature fruits and leaves extract of Iraqi christ’s thorn (IF-LCT). Synthesis of Ag /Ag2O NPs was verified by visual observation in which the AgNO3 solution turned to a brown-colored solution. The Ag/Ag2O NPs caused surface plasmon resonance (SPR) at 440 nm. Subsequent characterization was done by X-ray diffraction (XRD), ultraviolet-visible (UV-Vis), Fourier transform infrared (FTIR), field emission scanning electron microscope (FE-SEM) and energy dispersion X-ray spectroscopy (EDXS). The average crystallite size of the Ag/Ag2O NPs as assessed by XRD was determined to be 15.89 nm. All the other parameters approved synthesizes Ag/Ag2O NPs with a high surface area to volume ratio, high atomic packing factor (APF) and notably high specific surface area. FE-SEM analysis shown the silver NPs appeared as agglomerated spherical and quasi-spherical structure with average particles size equal to 21.65 nm. EDXS evidenced that nanoparticles contain silver and oxygen. The finest conditions for phytosynthesis of Ag NPs using aqueous extract to silver nitrate (1:10) ratio at 25 °C. The direct band gap was 2.96 eV. FTIR exhibited the particular stretch of bands of the synthesized Ag/Ag2O NPs. The aforementioned outcomes demonstrated that the Ag/Ag2O NPs were effectively prepared using IF-LCT extract